BRAND PERSONALITY CREATION THROUGH ADVERTISING (Study KFC on Television Commercial Break) - Mumu, Richard Laurenz; Pangemanan, Sifrid S. (Universitas Sam Ratulangi, 2016)
The perfect concept of Advertising and its application on the mass media cannot be separated with one central aspect from any sold product or certain service, named Brand personality and depends on five main aspects, which are Sincerity, Excitement, Competence, Ruggedness and Sophistication, especially for Kentucky Fried Chicken in Manado City.This research’s purposes are to figure out whether Brand Personality give significant influence to the Advertising of KFC at Manado City, simultaneously and to figure out whether Brand Personality give significant influence to the Advertising of KFC at Manado City, partially. To achieve those objectives, Multiple Regression Analysis is used. Its’ conclusions are Brand Personality generally give the significant influence for the Advertising of KFC and each Brand Personality partially give the significant influence for the Advertising of KFC. Based on the results, company’s managers and employees must maintain and enhance the good understanding about three Brand Personality, must improve customers’ understanding about Sophistication and Excitement, and must give more concern about other influencing factors of the customers’ understanding about the advertising and its contents. Keywords : brand personality, advertising